Techno-commercial feasibility of grid-tied solar system in philips morris pvt ltd (commercial building) of Pakistan - Manzoor, Zahid; Shahid, Zeeshan; Khan, Sheroz; Hwang, John Tan Teng (Institute of Electrical and Electronics Engineers Inc., 2018)
Pakistan is a developing country. The population of Pakistan is increasing day by day and due to increase in population the demand of electrical energy is also rising. Currently, Pakistan has a power generation gap of average 4500 to 5500 megawatt hour (MWh) [1]. The Renewable energy plays a vital role in such energy crisis by generating alternative power which is environmental friendly and reduces the carbon foot prints from the environment. The renewable energy sector that is solar, wind and hydro power is a very active area of research and there is a huge space available for modern industrial units and commercial buildings to fill the gap of energy generation and demand energy of Pakistan. In order to void that gap Philips Morris Pvt. ltd initiate with an on-grid solar system with Orient Energy Systems Pvt. ltd with a solar photovoltaic(PV) potential 151.2 kWp for first phase and it will extend up to 458.6 kWp in three phases. By installing solar system the firm saves to millions of rupees in bills of grid and also contributes towards green environment by reducing foot print of carbon dioxide emission from other power generation techniques. This paper provides a techno commercial feasibility of the implementation of the project and environmental friendly impact of such projects on global warming and ozone layer as well as the also shows that in future to reduce the dependency over energy sector and move towards self-reliance in generating greener and cleaner energy.